Frequency of Thyroid Dysfunction in Heart Failure Patients with Reduced Ejection Fraction - Amir Misbah ul Qamar, Muhammad; Abbas, Shahid; Khan, andaleeb; Ali, Ejaz; Butt, kamil Rehman; Rehman, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look for the frequency of thyroid dysfunction in heart failure patients with reduced ejection fraction at Medicine/Cardiology Department. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital Sialkot, from Nov 2019 to Apr 2020. Methodology: The sample population comprised of patients diagnosed with the heart failure and ejection fraction of 40% at Medicine/Cardiology unit. Patients underwent thyroid functions test from the laboratory of our hospital and were diagnosed as hypothyroid, hyperthyroid or euthyroid by consultant cardiologist and medical specialist. Age, gender, body mass index and New York heart association (NYHA) class were associated with thyroid dysfunction among the study participants. Results: Out of 110 patients with heart failure and low ejection fraction who underwent thyroid function testing during the study period, 92 (83.6%) patients were euthyroid, 14 (12.7%) had thyroid profile parameters showing hypothyroidism, while 04 (3.6%) had laboratory findings of hyperthyroidism. After chi-square, we found that patients with New York heart association class III and IV and high body mass index had a statistically significant relationship with thyroid dysfunction (pvalue 0.017 and <0.001 respectively) among the patients of heart failure with low ejection fraction. Conclusion: Thyroid dysfunction, especially hypothyroidism, emerged as a common finding among heart failure patients with low ejection fraction. Patients with New York heart association class III and IV and high body mass index should be considered high-risk and may be screened for thyroid problems if present with heart failure